Foamed resin heat-insulating material and method for producing same

By mixing negative thermal expansion material into the foam resin insulation material and integrating it with the fiber sheet, the thermal stress problem caused by the difference in linear expansion coefficients of metal and foam resin insulation material under extremely low temperature fluid flow is solved, and the effect of reducing cracks and improving safety is achieved.

CN119731249AActive Publication Date: 2025-03-28MEISEI INDUSTRIAL CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202380060809.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-30
Filing Date
2023-09-29
Publication Date
2025-03-28
Estimated Expiration
2043-09-29

AI Technical Summary

Technical Problem

In the case of extremely low temperature fluid circulation, the difference in linear expansion coefficient between metal and foamed resin insulation material leads to thermal stress, which easily produces cracks and increases the risk of explosion or fire.

Method used

The negative thermal expansion material is mixed into the foamed resin molded body and integrated with the fiber sheet composed of crossed warp and weft yarns. By combining the negative thermal expansion material and the fiber sheet, the difference in linear expansion coefficient is reduced and the expansion and contraction of the foamed resin insulation material is suppressed.

Benefits of technology

It effectively reduces the thermal stress generated by foamed resin insulation materials under extremely low temperature conditions, prevents cracks, improves safety, and reduces the risk of explosion or fire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731249A_ABST
    Figure CN119731249A_ABST
Patent Text Reader

Abstract

The present invention provides a foamed resin heat-insulating material and a method for manufacturing the same, which can reduce the difference between the linear expansion coefficients of the metal and the foamed resin heat-insulating material, thereby greatly reducing the thermal stress generated in the foamed resin heat-insulating material and preventing the generation of cracks. The foamed resin molded body is formed by foaming an unfoamed resin material mixed with a negative thermal expansion material which shrinks in volume along with temperature rise and expands in volume when the temperature drops. A fiber sheet comprising mutually intersecting warp yarns and weft yarns is integrated with the inner surface and the outer surface of the foamed resin molded body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a foamed resin thermal insulation material and a preparation method thereof. Background Art

[0002] In the past, when using foamed resin insulation materials to insulate fluid piping, fluid storage containers, etc., especially in the cold preservation of low-temperature fluids, foamed resin insulation materials with independent bubbles such as foamed rigid polyurethane resin are usually molded into a shape surrounding the piping and fluid storage containers.

[0003] However, when the temperature of a fluid changes while it is flowing, not only the pipes and storage containers but also the insulating material portions in contact with the pipes and storage containers are affected by the temperature change of the fluid and expand or contract.

[0004] Furthermore, pipes and storage containers are generally made of metal, but the coefficient of linear expansion of the foamed resin thermal insulation material is larger than that of metal.

[0005] In addition, when the fluid flowing through the piping or the fluid stored in the storage container is an extremely low-temperature fluid, for example, if the extremely low-temperature fluid is liquid nitrogen (LN2), it is -196°C, and if it is liquid hydrogen (LH2), it is -253°C. If air enters the gap at the interface between the piping or the storage container and the foamed resin insulation material, sometimes the oxygen in the air (liquefaction temperature -183°C) is liquefied and liquid oxygen is accumulated. The accumulated liquid oxygen may cause an explosion or fire due to the ignition of combustibles (for example, refer to Patent Document 1).

[0006] Therefore, it is considered to bond both of them with an adhesive so that no gap is formed between the pipe or storage container and the foamed resin insulation material.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 2016-176511 Summary of the invention

[0010] Problems to be solved by the invention

[0011] However, the linear expansion coefficient of SUS316L, which is a metal commonly used in pipes and storage containers, is α=10~16ppm / K (where ppm=1×10 -6), on the other hand, the linear expansion coefficient of the foamed polyurethane resin is α=50~60ppm / K. If the above-mentioned ultra-low temperature fluid circulates, due to the large difference in the linear expansion coefficients of the metal and the foamed resin insulation material, thermal stress acts on the insulation material and cracks are likely to occur. Air may enter through the cracks. Furthermore, if the ultra-low temperature fluid is liquid hydrogen, the above-mentioned problem is further aggravated because the liquefaction temperature of liquid hydrogen is -253°C.

[0012] Therefore, an object of the present invention is to solve the above-mentioned problem and reduce the difference in linear expansion coefficient between metal and foamed resin insulation, thereby minimizing the thermal stress generated in the foamed resin insulation and preventing the generation of cracks.

[0013] Means for solving problems

[0014] The first characteristic structure of the present invention is that it is composed of a foamed resin molded body formed by foaming an unfoamed resin material mixed with a negative thermal expansion material that shrinks in volume when heated and expands in volume when cooled.

[0015] According to the first characteristic configuration of the present invention, a negative thermal expansion material is mixed into the foamed resin molded body, so the negative thermal expansion material contracts as the temperature rises and expands based on the temperature drop. The negative thermal expansion material changes in expansion and contraction based on the temperature change of the fluid. As a whole, the expansion and contraction change of the foamed resin thermal insulation material is suppressed, and the difference in the linear expansion coefficient between the metal and the foamed resin molded body can be reduced.

[0016] Therefore, cracking of the foamed resin insulation material due to shrinkage of the pipe or storage container through which the cryogenic fluid flows can be prevented.

[0017] A second characteristic configuration of the present invention is that a fiber sheet composed of warp yarns and weft yarns intersecting each other is integrated with the inner surface and the outer surface of the foamed resin molded body.

[0018] According to the second characteristic configuration of the present invention, in addition to being able to achieve the above-mentioned effects of the first characteristic configuration of the present invention, the expansion and contraction changes of the foamed resin molded body based on temperature changes can be further suppressed by the resistance brought by the fiber sheet, and the difference in linear expansion coefficients between the metal and the foamed resin molded body can be further reduced.

[0019] A third characteristic configuration of the present invention is that the foamed resin molded body and a fiber sheet composed of warp yarns and weft yarns intersecting each other are integrated in a state of being stacked in layers.

[0020] According to the third characteristic configuration of the present invention, the fiber sheets composed of mutually intersecting warp and weft yarns are integrated in a layered state, so that the reinforcement generated by the fibers becomes larger in the two-dimensional direction, and the difference in linear expansion coefficient between the metal and the foamed resin molded body can be further reduced.

[0021] A fourth characteristic configuration of the present invention is that a plurality of the fiber sheets are integrated with the foamed resin molded body.

[0022] According to the fourth characteristic configuration of the present invention, the effect of suppressing expansion and contraction due to temperature changes can be enhanced also in the thickness direction by the multi-layered fiber sheets.

[0023] A fifth characteristic feature of the present invention is that cellulose nanofiber powder is mixed into the foamed resin molded body to form an integrated body.

[0024] According to the fifth characteristic configuration of the present invention, by mixing the cellulose nanofiber powder into the foamed resin molded body and integrating them together, the linear expansion coefficient of the foamed resin molded body is further reduced and can easily approach the linear expansion coefficient of metal.

[0025] The sixth characteristic configuration of the present invention is that the negative thermal expansion material is selected from zirconium tungstate phosphate (Zr2WO4(PO4)2), zirconium sulfate phosphate (Zr2SP2O 12 ), one of the oxide ceramics BiNi1-xFexO3 with a perovskite structure composed of bismuth-nickel-iron, zirconium tungstate (ZrW2O8), and silicon oxide (Li2O-Al2O3-nSiO2), the above-mentioned unfoamed resin material is one selected from unfoamed polyurethane resin, unfoamed polystyrene resin, unfoamed polyethylene resin, unfoamed polyester resin, and unfoamed phenolic resin, and the above-mentioned fiber sheet is a cloth selected from glass fiber, carbon fiber, and aromatic polyamide fiber.

[0026] The seventh characteristic configuration of the present invention is that the negative thermal expansion material is zirconium tungstate phosphate (Zr2WO4(PO4)2), the unfoamed resin material is an unfoamed polyurethane resin, the fiber sheet is a cloth composed of glass fibers, and the powder of cellulose nanofibers is mixed into the foamed resin molded body to form an integrated body, and more than 0.75 vol% of the negative thermal expansion material is mixed relative to the volume of the foamed resin molded body.

[0027] The eighth characteristic configuration of the present invention is that the negative thermal expansion material is zirconium tungstate phosphate (Zr2WO4(PO4)2), the unfoamed resin material is an unfoamed polyurethane resin, the fiber sheet is a cloth composed of glass fibers, and in the foamed resin molded body, 3wt% or more of cellulose nanofiber powder is mixed and integrated relative to the amount of filled unfoamed resin.

[0028] The ninth characteristic configuration of the present invention is that the negative thermal expansion material is zirconium tungstate phosphate (Zr2WO4(PO4)2), the unfoamed resin material is an unfoamed polyurethane resin, the fiber sheet is a cloth composed of glass fibers, and in the foamed resin molded body, 1wt% or more of cellulose nanofiber powder is mixed and integrated relative to the amount of filled unfoamed resin, and further, multiple layers of fiber sheets composed of mutually crossed warp and weft yarns are integrated with each other, and 0.75vol% or more of the negative thermal expansion material is mixed relative to the volume of the foamed resin molded body.

[0029] According to the ninth characteristic configuration of the present invention, the mutually integrated multi-layer fiber sheets are integrated with the foamed resin molded body, whereby the linear expansion coefficient can be easily made close to that of metal even if the mixed amounts of cellulose nanofibers and negative thermal expansion material are small.

[0030] The characteristic structure of the tenth manufacturing method of the present invention is that a negative thermal expansion material composed of zirconium tungstate phosphate (Zr2WO4(PO4)2) is mixed into an unfoamed polyurethane resin, and the unfoamed resin material in this state is filled into a mold in a manner of stacking with a fiber sheet of glass cloth composed of intersecting warp and weft yarns, and is foamed and cured in the mold to form a shape. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a cross-sectional view of a fluid transport piping.

[0032] Figure 2 This is a curve diagram showing the change in linear expansion coefficient caused by the change in the amount of negative thermal expansion material added.

[0033] Figure 3 It is a longitudinal cross-sectional view of a foamed resin thermal insulation material.

[0034] Figure 4 It is a graph showing the change line of the linear expansion coefficient.

[0035] Figure 5 It is a graph showing the change line of the linear expansion coefficient.

[0036] Figure 6 It is a graph showing the change lines of each linear expansion coefficient.

[0037] Figure 7 It is a graph showing the change lines of each linear expansion coefficient.

[0038] Figure 8 It is a graph showing the change lines of each linear expansion coefficient.

[0039] Fig. 9 It is a graph showing the change lines of each linear expansion coefficient.

[0040] Fig.10 This is a schematic perspective view of a test body using the foamed resin thermal insulation material a in a liquid nitrogen immersion test.

[0041] Fig.11 This is a schematic perspective view of a test body using a foamed resin thermal insulation material b in a liquid nitrogen immersion test.

[0042] Fig.12 , (a) is a longitudinal sectional side view of a 2B piping cooling verification model using liquid nitrogen, (b) is an AA longitudinal sectional view in (a), and (c) is a BB longitudinal sectional view in (a).

[0043] Fig.13 yes Fig.12 A partial enlarged view of (a).

[0044] Fig.14 It is a table showing various physical property values.

[0045] Fig.15 is a table showing the results of FEM stress analysis.

[0046] Fig.16 is a temperature distribution table showing the verification test results.

[0047] Fig.17 In the figure, (a) is a temperature change table of the foamed resin insulation material a, and (b) is a temperature change table of the foamed resin insulation material b.

[0048] Fig.18 In the figure, (a) is a curve diagram showing the variation of the strain amount of the foamed resin thermal insulation material a, and (b) is a curve diagram showing the variation of the strain amount of the foamed resin thermal insulation material b.

[0049] Fig.19 This is a table showing thermal stress calculated from the strain amount.

[0050] Fig. 20 , (a) is a longitudinal cross-sectional view of a 2B pipe cooling verification model using liquid helium, and (b) is a longitudinal cross-sectional view along line CC in (a).

[0051] Fig.21 It is a table showing various physical property values.

[0052] Fig. 22 is a table of FEM stress analysis results.

[0053] Fig.23 is a table showing temperature distribution indicating verification test results.

[0054] Fig.24 Graphs showing temperature changes, (a) is a graph showing the temperature change in the first cooling, and (b) is a graph showing the temperature change in the second cooling.

[0055] Fig.25 It is a graph which shows the change of the strain amount in the cooling test.

[0056] Fig.26 is a table showing stress calculated from the strain amount.

[0057] Fig. 27 This is a partial enlarged view of a foamed resin molded body.

[0058] Fig.28 It is a graph showing the change of the linear expansion coefficient of the test results.

[0059] Fig.29 Among them, (A) is an exploded perspective view showing the concept of the adhesive integration method, and (B) is an exploded perspective view showing the concept of the multi-layer injection integration method.

[0060] Fig.30 This is a longitudinal sectional perspective view of a foamed resin molded body according to another embodiment. DETAILED DESCRIPTION

[0061] Hereinafter, embodiments of the present invention will be described based on the drawings.

[0062] For metal fluid delivery piping and fluid storage containers connected to the piping, in order to keep the delivered fluid warm or cold, their entire circumference is surrounded by a foam resin insulation material to keep them cold or warm, such as Figure 1 , a cross-sectional structure of a pipe is shown as an example.

[0063] As the metal forming the above-mentioned piping and storage container, SUS316L is often used as an example for transporting extremely low temperature fluids such as liquefied natural gas (LNG) and liquid nitrogen (LN2). The linear expansion coefficient α of this metal is 10 to 16 ppm / K (where ppm = 1×10 -6 ).

[0064] The foamed resin thermal insulation material is formed by stacked cold-insulating materials a, b and c. In particular, the cold-insulating material a connected to the metal pipe P is prepared by mixing a white powder (manufactured by Nippon Chemical Industry Co., Ltd. (trade name "cerafit")) composed of crystals of zirconium tungstate phosphate (Zr2(WO4)(PO4)2) as a negative thermal expansion material into an unfoamed polyurethane resin (linear expansion coefficient of the foamed resin molded body α=50-60ppm / K) commonly used as a foamed resin thermal insulation material for low temperatures, and foaming the unfoamed polyurethane resin in this state to form a shape along the outer surface of the pipe P or a storage container.

[0065] In order to foam the above-mentioned polyurethane resin, a foaming agent such as carbon dioxide (water formula-PUF), HFC-PUF, HFO-PUF, etc. is used. However, in the present application, the cold insulation material a is formed by polyurethane foam using carbon dioxide foaming, and the polyol to which water is added as a foaming agent reacts with isocyanate to produce carbon dioxide for foaming molding.

[0066] It should be noted that the cold-insulating material b and the cold-insulating material c may be any one of water-formulated-PUF, HFC-PUF and HFO-PUF.

[0067] In addition, depending on the state of foaming, the smaller the density of the molded product, the smaller the thermal conductivity. However, when the density is extremely small, the bubble film becomes thinner or the number of continuous bubbles increases, so the radiation heat transfer increases, and the influence of convection occurs, and the thermal conductivity increases instead.

[0068] Generally speaking, the density is 50kg / m 3 When , the thermal conductivity is minimum.

[0069] The linear expansion coefficient of the above-mentioned zirconium tungstate phosphate crystal is shown to be -3ppm / K. The bond between the metal and oxygen atoms is strong, so it is not easy for the volume expansion of each unit itself caused by heating to occur. The bond angle between each unit is deformed in the direction of reducing the spatial volume within the structure. Therefore, the crystal as a whole is a material that thermally shrinks roughly linearly with the increase of temperature in a wide temperature range.

[0070] It should be noted that a white powder (manufactured by Nippon Chemical Industry Co., Ltd. (trade name "cerafit") consisting of crystals of zirconium tungstate phosphate (Zr2(WO4)(PO4)2) as the negative thermal expansion material) with a specific surface area of ​​0.2 m 2 / g, D50 = 18.7 μm, bulk density 1300 kg / m 3 The temperature range of -100 to 800°C shows a linear expansion coefficient of α = -3 ppm / K.

[0071] [Experimental Example 1]

[0072] Then, if Figure 2 As shown in the graph of , the change in the linear expansion coefficient due to the change in the amount of the negative thermal expansion material added to the foamed polyurethane resin foam molded product was measured.

[0073] It should be noted that B in the figure represents each measurement point.

[0074] According to the measurement results, SUS316L, which is a metal material for piping, storage containers, etc., is 16ppm / K (line M in the figure). In contrast, it is 51.4ppm / K when no negative thermal expansion material is added. It can be predicted from the curve that if the amount of negative thermal expansion material added is increased, the linear expansion coefficient of the foamed molded body decreases linearly, and if it is 14 to 15vol% relative to the volume of the foamed resin molded body, it is close to the linear expansion coefficient of the above-mentioned metal material (on the line M in the figure).

[0075] It should be noted that the amount of the negative thermal expansion material added is calculated based on the bulk specific gravity of the negative thermal expansion material.

[0076] [Experimental Example 2]

[0077] Then, if Figure 3 As shown in the longitudinal cross-sectional view of the foamed resin insulation material, a foamed resin insulation material is manufactured in which a layer of glass cloth GC composed of mutually crossed warp yarns and weft yarns is foamed and molded in a manner that is integrated with the outer surface (front and back) of the foamed polyurethane resin (PUF), and the change in the linear expansion coefficient of the foamed resin insulation material (cold insulation material) a with a layer of glass cloth integrated and the foamed resin insulation material (cold insulation material) b without glass cloth based on the change in the amount of negative thermal expansion material added is investigated, and the result is shown in Figure 4 Graph of the curve.

[0078] Thus, by integrating a layer of glass cloth GC, the overall thermal expansion is reduced by about 36% even without adding negative thermal expansion material (each measuring point B), and when the amount of negative thermal expansion material added is 10 vol% relative to the volume of the foamed resin molded body (each measuring point A), it is further reduced by about 26%.

[0079] [Experimental Example 3]

[0080] Then, if Figure 5 As shown, the influence of the number of laminated glass cloths GC was investigated, and a change line G (an approximate line of each measurement point G) was obtained.

[0081] It can be seen from this that by laminating two sheets of glass cloth GC on the surface of the foamed resin insulation material, even without adding a negative thermal expansion material, the linear expansion coefficient of the SUS316L metal (the line M in the graph) is quite close, for example, to aluminum (linear expansion coefficient α = 24 ppm / K) ( Figure 5 The Al line in the sample is lower than that in the sample (20.5ppm / K).

[0082] [Experimental Example 4]

[0083] When the number of layers of glass cloth GC integrated with foamed polyurethane resin (PUF) is one layer and two layers, the change of linear expansion coefficient α due to the change of the amount of negative thermal expansion material added is investigated, and the change line G1 (the change line of each measurement point G1) when one layer is used and the change line G2 (the change line of each measurement point G2) when two layers are used are shown in FIG. Figure 6 .

[0084] It can be seen from the change line G2 that when the amount of the negative thermal expansion material added is 0.75 to 1 vol % relative to the volume of the foamed resin molded body, the linear expansion coefficient α decreases sharply.

[0085] It should be noted that, in the figure, M is the linear expansion coefficient of SUS316L, and Al is the linear expansion coefficient of aluminum.

[0086] [Experimental Example 5]

[0087] Next, the change in the linear expansion coefficient α caused by adding cellulose nanofibers (CNF) to the foamed polyurethane resin (PUF) is plotted as a graph. Figure 7 .

[0088] Figure 7 In the figure, the first change line G0 when the addition amount of cellulose nanofiber (CNF) is changed relative to the foamed polyurethane resin without glass cloth GC, the second change line G1 when the addition amount of cellulose nanofiber (CNF) is changed relative to the foamed polyurethane resin that integrates the glass cloth GC into one layer, and the third change line G2 when the addition amount of cellulose nanofiber (CNF) is changed relative to the foamed polyurethane resin that integrates the glass cloth GC into two layers are plotted as curves.

[0089] In the figure, for comparison, a line Al indicating the linear expansion coefficient of aluminum and a linear expansion coefficient α=16 ppm / K of metal SUS316L (line M in the figure) are shown.

[0090] This shows that the linear expansion coefficient approaches that of metal SUS316L by adding 3 wt % of cellulose nanofiber (CNF) to the amount of polyurethane resin in which two layers are integrated with each other with respect to the glass cloth GC.

[0091] The cellulose nanofiber (CNF) used is a product name (S-CNF (water-soluble)) manufactured by Yokogawa Bio Frontier, which is generally 1 / 5 of the lightness of iron, 5 times the strength of iron, and has a linear expansion coefficient of α=0.1 to 0.2 ppm / K (0 to 100°C).

[0092] [Experimental Example 6]

[0093] The change curve of the linear expansion coefficient α when the glass cloth GC is integrated into one layer for the foamed polyurethane resin and the amount of cellulose nanofiber (CNF) added thereto is changed is shown in FIG. Figure 8 The graph shows a change line C0 when the amount of negative thermal expansion material added is 0 vol%, a change line C1 when the amount of negative thermal expansion material added is 2 vol%, and a change line C2 when the amount of negative thermal expansion material added is 4 vol%.

[0094] [Experimental Example 7]

[0095] The variation curve of the linear expansion coefficient α when the glass cloth GC is integrated into two layers with respect to the foamed polyurethane resin and the amount of cellulose nanofiber (CNF) added thereto is changed is shown in FIG. Fig. 9 The change line D0 when the negative thermal expansion material is added in an amount of 0 vol%, the change line D1 when the negative thermal expansion material is added in an amount of 0.25 vol%, the change line D2 when the negative thermal expansion material is added in an amount of 0.5 vol%, the change line D3 when the negative thermal expansion material is added in an amount of 0.75 vol%, the change line D4 when the negative thermal expansion material is added in an amount of 1 vol%, the change line D5 when the negative thermal expansion material is added in an amount of 2 vol%, and the change line D6 when the negative thermal expansion material is added in an amount of 4 vol%.

[0096] It can be seen from this that by integrating the multilayer fiber sheet with the resin, adding cellulose nanofibers (CNF) at a level of 1 wt% or more, and mixing in 0.75 vol% or more of negative thermal expansion material, it is possible to approach the linear expansion coefficient of metal SUS316L α = 16 ppm / K (on the M line in the figure).

[0097] [Experimental Example 8] Liquid nitrogen (LN2) immersion test

[0098] like Fig.10 As shown in FIG. 1 , a foamed resin insulation material of 200×25×25 mm was prepared by foaming and molding two layers of glass cloth GC composed of intersecting warp and weft yarns and the outer surface (front and back) of foamed polyurethane resin (PUF) in a manner of being integrated, and a foamed resin insulation material a in which two layers of glass cloth were integrated and mixed with a negative thermal expansion material added in an amount of 1 vol%, and a Fig.11 The foamed resin insulation material b shown in the figure without adding negative thermal expansion material and glass cloth GC is bonded with foamed resin insulation material a or foamed resin insulation material b on one side of a 200×25×25mm SUS316 L prism M using a polyurethane adhesive and cured, and the resulting material is used as a test body.

[0099] It should be noted that in the foamed resin insulation material a, the glass cloth surface is bonded to the SUS316L prism M. These test bodies were subjected to a 5-day cycle test: they were completely immersed in liquid nitrogen (-196°C) for 8 hours and then left at room temperature to confirm whether cracks were generated in the foamed resin insulation material (PUF) at the bonding interface or near the interface due to the difference in linear expansion coefficient between the foamed resin insulation material and SUS316L.

[0100] As a result of the liquid nitrogen (LN2) immersion cycle test, the foamed resin thermal insulation material b had peeling E ( Fig.11 ), breakage of PUF, no peeling at the bonding interface, cracking of the foamed polyurethane resin (PUF) and other deformation were found in the foamed resin insulation material a.

[0101] In the FEM stress analysis using SolidWorks Simulation manufactured by Dassault Systemes SolidWorks Corporation, the principal stress produced the maximum stress at the four vertices of the bonding surface, but the safety factor of the foamed resin insulation material b in this portion was 0.4 times, resulting in cracks, while the safety factor of the foamed resin insulation material a was 1.2 times, resulting in no cracks, which is consistent with the result of this immersion in liquid nitrogen (-196°C).

[0102] [Experimental Example 9] Pipe cooling test using liquid nitrogen (LN2) at -196°C for 2B pipe (SUS316L)

[0103] (2B piping cooling verification model production)

[0104] like Fig.12 (a), (b), (c), Fig.13 As shown, the pipe is SUS316L of 2B (A nominal 50A, pipe outer diameter 60.5 mm) × 4,000 mm based on JIS standard.

[0105] The cold insulation structure is set to a three-layer structure. The cold insulation thickness is calculated based on the conditions that the external air temperature is 30°C and the relative humidity is 85%, there is no condensation on the outer surface of the cold insulation material, and the interface temperature between the first and second layers of the cold insulation material is above the liquefied natural gas (LNG) temperature (-163°C). The cold insulation thickness is 10 mm for the first layer, 40 mm for the second layer, and 60 mm for the third layer.

[0106] In order to give the pipe cover moisture-proof / waterproof properties, an aluminum kraft paper sheet attached with two layers of glass cloth (Unitika Co., Ltd. product, model: L55MN104F, cloth type: gauze structure, 2.5mm mesh) is set on the inner surface of the concave steel mold for making the pipe cover. In addition, two layers of glass cloth are set on the convex part of the steel mold, and a water-formulated polyurethane resin added with a negative thermal expansion material of 1 vol% relative to the injection volume is injected for foaming, molding and integration with the glass cloth. The material obtained is used as the foamed resin insulation material a of the first layer of the cold-keeping material.

[0107] As a comparison object, a foamed resin insulation material b of the foamed resin molded body 1 was a material having an aluminum kraft paper sheet on the outer surface, no glass cloth on the inner surface, and no negative thermal expansion material added.

[0108] For two SUS316L 2B pipes (4,000 mm), Fig.13 As shown, the foamed resin insulation material a and the foamed resin insulation material b of the foamed resin molded body 1 as the first layer are respectively bonded to the outer surface of the piping P by using a polyurethane resin-based adhesive 2 on the entire surface, and the joints along the circumferential direction between the foamed resin insulation materials a or between the foamed resin insulation materials b are also bonded to the entire surface by using a polyurethane resin-based adhesive 2.

[0109] In addition, a butyl moisture-proof tape 5 is attached to the circumferential and longitudinal joints of the one-layer foamed resin molded body 1 .

[0110] The second and third layers of the cold-insulating material foamed resin molded body 1 are water-formulated polyurethane foams without glass cloth and negative thermal expansion materials, with the inner surface made of kraft paper and the outer surface made of aluminum kraft paper sheets.

[0111] The second layer of foamed resin molded body 1 is coated with a polyurethane adhesive 7 at a diameter of 30 to 50 mm at the center of the inner surface, and partially adhered to the outer surfaces of the first layer of foamed resin insulation a and foamed resin insulation b.

[0112] It should be noted that the circumferential and longitudinal joints between the foamed resin molded bodies 1 of the second layer are hollow joints without an adhesive.

[0113] Moreover, similarly to the first layer, butyl moisture-proof tapes 5 are attached to the circumferential and longitudinal joints of the foamed resin molded body 1 of the second layer.

[0114] Next, for the purpose of moisture-proofing and waterproofing, a polyethylene sheet 3 is wound in a spiral shape on the outer surface of the second-layer foamed resin molded body 1, and the third-layer foamed resin molded body 1 is mounted thereon.

[0115] The circumferential seams and longitudinal seams of the third-layer foamed resin molded body 1 are also fully bonded using a polyurethane resin-based adhesive 4, and butyl moisture-proof tape 5 is attached to the seams along the circumferential direction and longitudinal direction of the third-layer foamed resin molded body 1. The circumferential direction is tightened with a stainless steel belt to assemble a pipe cooling verification model.

[0116] It should be noted that if Fig.12 (a) Fig.12 (b) Fig.12 As shown in (c), in order to measure the shrinkage caused by cooling, strain gauges are attached to the outer surface of the pipe, the inner surface of the foamed resin insulation material a and the foamed resin insulation material b, and in order to obtain the temperature of each part, a thermocouple is also configured.

[0117] In order to shrink the SUS316L pipe during cooling, one end of the pipe in the longitudinal direction is made a fixed end 8 and the other end of the pipe is made a free end 9 .

[0118] (FEM stress analysis in 2B piping model)

[0119] FEM stress analysis was used to confirm whether the tensile thermal stress generated in the first-layer foamed resin molded body (foamed resin insulation materials a, b) when the SUS316L pipe was filled with -196°C (liquid nitrogen) caused cracks in the first-layer foamed resin molded body 1.

[0120] It should be noted that the FEM stress analysis was performed using SolidWorks Simulation manufactured by Dassault Systèmes SolidWorks Corporation. In addition, various physical property values ​​were calculated using Table ( Fig.14 ) shown in the .

[0121] It should be noted that Fig.14 The θ in represents the temperature.

[0122] As a result of FEM stress analysis, the average generated thermal stress (tensile stress in the pipe axial direction) generated in the foamed resin molded body (foamed resin insulation material b) without adding a negative thermal expansion material in the pipe 2B was 0.48 MPa, and the safety factor was 1.5.

[0123] For the maximum tensile stress of 0.85 MPa, the safety factor is 0.8 which is less than 1.

[0124] From the maximum tensile stress, cracks may occur in the foamed resin molded body 1 ( Fig.15 ).

[0125] On the other hand, the average generated thermal stress in the foamed resin molded body (foamed resin thermal insulation material a) to which the negative thermal expansion material was added and integrated with two layers of glass cloth was 0.35 MPa, and the safety factor was 4.5.

[0126] The maximum tensile stress is 1.3 MPa, and the safety factor is 1.2, which is the calculation result that the foamed resin insulation material a does not produce cracks ( Fig.15 ).

[0127] (Overview of cooling test in 2B piping verification model)

[0128] Liquid nitrogen (LN2) was introduced into the pipe P to cool the pipe until the temperature of each part was stabilized. After about 30 hours, the supply of liquid nitrogen (LN2) was stopped, and the temperature was naturally raised to return to normal temperature.

[0129] Liquid nitrogen (LN2) was introduced into the pipe P again to perform secondary cooling until the temperature of each part was stabilized. After about 30 hours, the temperature was naturally raised and returned to room temperature. The test body was disassembled and cracks in the foamed resin insulation material a or b were confirmed.

[0130] (2B piping cooling verification test results)

[0131] like Fig.16 , Fig.17 (a) Fig.17 As shown in (b), in the foamed resin insulation material a or b, the temperature distribution in the steady state during the cooling test is substantially equal to the FEM calculated value.

[0132] like Fig.18 As shown in (a) and (b) of 18, it can be confirmed from the measurement results of the strain amount during cooling that the strain amount of SUS316L and the strain amount of the foamed resin insulation material a show approximately the same behavior ( Fig.18 (a)), that is, the foamed resin insulation material a follows the action of SUS316L.

[0133] On the other hand, it can be confirmed that the foamed resin insulation material b has a large strain relative to SUS316L from the temperature of the pipe P to about -120°C, and the foamed resin insulation material b cannot follow the SUS316L ( Fig.18 (b)).

[0134] It should be noted that, based on the use of Fig.12 (b) Fig.12 The values ​​measured by the temperature sensors (A to H) shown in (c) are plotted in a graph. Fig.17 (a) Fig.17 As shown in the curve (b), 10 in the figure indicates Fig.12(a) The horizontal positions of the tube surface A, B and Fig.12 The measured values ​​of the upper C and lower D of the tube surface of (c), 11 represents Fig.12 The measured value of point E of (c), 12 represents Fig.12 The measured value of point F of (c) is 13. Fig.12 The measured values ​​of points G and H in (c).

[0135] As a result of the disassembly inspection, in the foamed resin insulation material a, no deformation such as cracks in the foamed polyurethane resin (PUF) and peeling of the adhesive 2 between the pipe P and the first layer of the foamed resin insulation material a was observed. On the other hand, in the foamed resin insulation material b, cracks in the foamed polyurethane resin (PUF) and deformation such as swelling and peeling of the adhesive 2 between the pipe P and the first layer of the foamed resin insulation material b were observed, indicating that the adhesion to SUS316L was not good.

[0136] like Fig.19 As shown, in addition, regarding the thermal stress near the boundary between the pipe P and the foamed resin insulation material a, which can be calculated from the strain, as an analysis result, the average thermal stress generated (tensile stress in the axial direction of the pipe) is 0.40 MPa (strain - 2,587 μST), which is the same result as the value previously obtained by FEM analysis (VonMises stress, 0.40 MPa), suggesting the appropriateness of the present pipe cooling test and the safety factor of more than 1.4 for the maximum value of the VonMises stress as the previous result.

[0137] [Experimental Example 10] Pipe cooling test using liquid helium (LHe) (-269°C) for 2B pipe (SUS316L)

[0138] (2B piping cooling verification model production)

[0139] like Fig. 20 (a), (b), Fig.13 As shown, the pipe is SUS316L of 2B (A nominal 50A, pipe outer diameter 60.5 mm) × 2,000 mm based on JIS standard.

[0140] The cold insulation structure is set to a three-layer structure. The cold insulation thickness is calculated based on the conditions that the external air temperature is 30°C and the relative humidity is 85%, there is no condensation on the outer surface of the cold insulation material, and the interface temperature between the first and second layers of the cold insulation material is above the liquefied natural gas (LNG) temperature (-163°C). The cold insulation thickness is 15 mm for the first layer, 50 mm for the second layer, and 50 mm for the third layer.

[0141] It should be noted that the 2B pipe cooling verification model was prepared using the same procedure as in Experimental Example 9.

[0142] In order to measure the amount of contraction due to cooling, strain gauges were attached to the outer surface of the pipe and the inner surface of the foamed resin insulation material a, and thermocouples were also arranged to obtain the temperature of each part.

[0143] However, a platinum / cobalt temperature measuring resistor capable of measuring the temperature of liquid helium (LHe) (-269° C.) is provided on the piping side.

[0144] In order to shrink the SUS316L pipe during cooling, one end is used as a fixed end 8 and the other end is used as a free end 9 ( Fig. 20 ).

[0145] (FEM stress analysis in 2B piping model)

[0146] By FEM stress analysis, it was confirmed that the tensile thermal stress generated in the foamed resin molded body (foamed resin insulation material a) of the first layer when the inside of the SUS316L pipe was filled with -269°C (liquid helium) caused the thermal stress generated in the foamed resin molded body of the first layer.

[0147] It should be noted that the FEM stress analysis was performed using SolidWorks Simulation manufactured by Dassault Systèmes SolidWorks Corporation.

[0148] In addition, various physical property values ​​are used Fig.21 The values ​​shown in the table.

[0149] It should be noted that Fig.21 The θ in represents the temperature.

[0150] The FEM stress analysis results are shown in Fig. 22 in the table.

[0151] The average generated thermal stress (VonMises) generated in the foamed resin molded body (foamed resin thermal insulation material a) in which a negative thermal expansion material is added to the pipe 2B and integrated with two layers of glass cloth is 0.52 MPa, and the safety factor is 3.6.

[0152] The maximum tensile stress is 1.73 MPa and the safety factor is 1.1, which is a calculation result indicating that no cracks occur in the foamed resin insulation material a.

[0153] (Overview of cooling test in 2B piping verification model)

[0154] First, regarding the cooling of the pipe P, liquid nitrogen (LN2) was introduced into the pipe as preliminary precooling, and cooling was performed for about 48 hours until the temperature of each part was stabilized.

[0155] Thereafter, the supply of liquid nitrogen (LN2) was stopped, and the liquid nitrogen (LN2) filling the pipe P was forcibly extracted, and then liquid helium (LHe) was introduced to cool the pipe to -269°C, and this temperature was maintained for 2 hours.

[0156] After that, the temperature was naturally raised to normal temperature. Liquid nitrogen (LN2) was introduced into the pipe P again to perform preliminary precooling, and liquid helium (LHe) was used to perform main precooling, and a second cooling test was performed.

[0157] The temperature was naturally raised and returned to room temperature, then the test body was disassembled to check for cracks and the like in the foamed resin thermal insulation material a.

[0158] (2B piping cooling verification test results)

[0159] like Fig.23 , Fig.24 (a) Fig.24 As shown in (b), the temperature distribution in the steady state during the cooling test is approximately equal to the FEM temperature analysis value.

[0160] like Fig.25 As shown, from the measurement results of the strain amount during the cooling test, it can be confirmed that the strain amount of SUS316L and the strain amount of the foamed resin thermal insulation material a show substantially the same behavior, that is, the foamed resin thermal insulation material a follows the behavior of SUS316L.

[0161] As a result of the disassembly inspection, no cracks were observed in the foamed resin heat insulating material a, and no deformation such as peeling of the adhesive 2 between the pipe P and the first layer of the foamed resin heat insulating material a was observed.

[0162] It should be noted that Fig.24 The measurement curves 14 to 17 shown in (a) and (b) of FIG. 24 are based on Fig.12 (b) Fig.12 The values ​​measured by the temperature sensors (A to H) shown in (c) are plotted in a graph. Fig.24 In (a) and (b) 24, 14 represents the measured values ​​of points A and C on the piping surface, 15 represents the measured value of point E between layers 1 and 2 of the PUF cover, 16 represents the measured value of point F between layers 2 and 3 of the PUF cover, and 17 represents the measured values ​​of points G and H of the outer surface of the third layer of the PUF cover and the external air temperature.

[0163] like Fig.26As shown, in addition, regarding the thermal stress near the boundary between the pipe P and the foamed resin insulation material a, which can be calculated from the strain, as an analysis result, the average thermal stress (tensile stress in the axial direction of the pipe) is 0.50 MPa (strain - 3,303 μST), which is roughly the same result as the value previously obtained by FEM analysis (Von Mises stress, 0.52 MPa), suggesting the appropriateness of the present pipe cooling test and the safety factor of more than 1.3 for the maximum value of the Von Mises stress as the previous result.

[0164] [Experimental Example 11] Reinforcement effect of glass cloth when the thickness of polyurethane foam (PUF) is changed

[0165] like Fig. 27 As shown, in order to minimize the thermal stress generated in the foamed resin insulation material at extremely low temperatures and prevent the occurrence of cracks in the foamed polyurethane (PUF), there is a method of integrating a fiber sheet composed of mutually intersecting warp and weft yarns with the end portion in the thickness direction of the foamed resin molded body 1 for reinforcement.

[0166] At this time, if the distance between glass cloths is L, when L is large, it is expected that the reinforcing effect of the glass cloth GC is particularly weak in the central portion (L / 2) of the reinforced foamed resin molded body 1.

[0167] Using the thickness of the foamed polyurethane (PUF), i.e. the distance L between the fiber sheets, as a parameter, the integrated foamed polyurethane (PUF) of the fiber sheets (two layers) was molded and the linear expansion coefficient (normal temperature to -170°C) was measured, and an approximate formula (correlation coefficient 0.989) was obtained using the Gompertz curve as a representative example of the growth curve.

[0168] It should be noted that the fiber sheet (glass cloth) used was a product of Unitika Co., Ltd. (product number: L55MN104F, fabric type: leno weave, 2.5 mm mesh).

[0169] like Fig.28 As shown in FIG. 1 , the test results confirm that as the distance L between the fiber sheets increases, the linear expansion coefficient α increases. When L=200 mm or more, the linear expansion coefficient α approaches 51.9 ppm / K of the polyurethane foam (PUF) not reinforced with the fiber sheets.

[0170] In order to prevent cracks in polyurethane foam (PUF) at extremely low temperatures, if the linear expansion coefficient of various metals (SUS316L, α=10~16ppm / K) is taken into account, the distance between glass cloths is assumed to be L=15mm or less (as the linear expansion coefficient, α≒20ppm / K). In the glass cloth integrated polyurethane foam (PUF) with L>15mm, the linear expansion coefficient becomes large. When used as the first layer of cold insulation material for liquid nitrogen and liquid hydrogen piping / equipment, polyurethane foam (PUF) may crack.

[0171] In order to avoid this, the following experiment was conducted.

[0172] like Fig.29 As shown in (B), fiber sheets are stacked at a spacing of L = 15 mm, injected and foamed and layered in sequence, and glass cloth is injected and integrated in a manner such that the thickness of the foamed polyurethane (PUF) is t = 30 (15 / 15), 45 (15 / 15 / 15), and 60 (15 / 15 / 15 / 15) mm to produce a multilayer test body, and the linear expansion coefficient is measured.

[0173] It should be noted that, for reference, Fig.29 As shown in (A), when the thickness of the polyurethane foam (PUF) was t=30 (15 / 15), the integration method using an adhesive was also evaluated.

[0174] like Fig.28 As shown, the linear expansion coefficient in the multi-layer injection integration method is 17.9, 19.2, and 19.1 ppm / K at t=30, 45, and 60 mm, respectively, which is approximately the same as the linear expansion coefficient α=17.7 ppm / K of the glass cloth integrated PUF (single layer) with a thickness of t=15 mm.

[0175] On the other hand, the polyurethane foam (PUF) with a thickness of t=30 (15 / 15) mm produced using an adhesive has a linear expansion coefficient of 31.0 ppm / K due to the influence of the adhesive, which is about 1.7 times that of the multi-layer integrated method.

[0176] In the cold insulation design of piping / equipment for liquid nitrogen and liquid hydrogen, the design concept is to make the interface temperature of the first layer of foamed resin insulation material and the second layer of foamed polyurethane (PUF) above the liquefied natural gas (LNG) temperature (-163°C). Therefore, when the piping size becomes larger, the cold insulation thickness of the first layer of foamed insulation material increases. For example, in a 24B piping, the cold insulation thickness is 37mm. When the distance between glass cloths L = 37mm, the linear expansion coefficient of the foamed resin insulation material becomes larger (α≒27ppm / K), and the foamed polyurethane (PUF) may crack at extremely low temperatures.

[0177] On the other hand, if in a multi-layer integration approach ( Fig.29 In (B)), when a foamed resin insulation material with t=45 (15 / 15 / 15) mm is applied, the linear expansion coefficient does not change compared with the single layer with L=15 mm, so cracks in the PUF can be suppressed.

[0178] [Other embodiments]

[0179] Other embodiments are described below.

[0180] <1> As an example of the foamed resin for molding, polyurethane resin (PUF) is used, but it can also be a foam of polyisocyanurate (PIR) or phenolic resin. In addition, as the unfoamed resin material, it can also be an unfoamed polystyrene resin, an unfoamed polyethylene resin, or an unfoamed polyester resin.

[0181] <2> As the negative thermal expansion material, zirconium phosphate sulfate (Zr2SP2O4) may be used instead of zirconium tungstate phosphate (Zr2WO4(PO4)2) (manufactured by Nippon Chemical Industry Co., Ltd.). 12 ) (manufactured by Tokyo Institute of Technology), oxide ceramic BiNi1-xFexO3 with a perovskite structure composed of bismuth-nickel-iron, zirconium tungstate (ZrW2O8) (manufactured by JX Metals Co., Ltd.), silicon oxide (Li2O-Al2O3-nSiO2), zirconium phosphate (Zr(HPO4)2) (manufactured by Toagosei Co., Ltd.).

[0182] <3> When the above-mentioned fiber sheets are stacked with multiple sheets of glass cloth whose warp yarns and weft yarns are crossed with each other, for example, the warp yarns of the first sheet of glass cloth and the warp yarns of the second sheet of glass cloth can be stacked in a manner that obliquely crosses each other. In addition, for the material of each fiber sheet, carbon fiber, aramid fiber, etc. can be selected instead of glass cloth.

[0183] <4> The foamed resin molded body may be formed by filling an unfoamed resin into a mold, foaming it, and solidifying it, or by spraying it with a sprayer.

[0184] <5> The foamed resin molded body and the fiber sheet composed of warp yarns and weft yarns intersecting each other may be formed by Fig.29 (B), a method in which the glass cloth is arranged in a layer in a mold and an unfoamed resin is filled into the mold for foaming and curing, such as Fig.30 As shown, it is formed by being buried in a layer within the thickness of the foamed resin.

[0185] It should be noted that, as described above, symbols are given for the convenience of comparison with the drawings, but the present invention is not limited to the structure of the drawings by this description. In addition, it is of course possible to implement in various forms within the scope of the gist of the present invention.

Claims

1. A foamed resin thermal insulation material, comprising a foamed resin molded body formed by foaming an unfoamed resin material mixed with a negative thermal expansion material that contracts in volume when heated and expands in volume when cooled.

2. The foamed resin thermal insulation material according to claim 1, wherein: A second characteristic configuration of the present invention is that a fiber sheet composed of warp yarns and weft yarns intersecting each other is integrated with the inner surface and the outer surface of the foamed resin molded body.

3. The foamed resin thermal insulation material according to claim 1, wherein: The foamed resin molded body is integrated with a fiber sheet composed of warp yarns and weft yarns intersecting each other in a layered state.

4. The foamed resin thermal insulation material according to claim 3, wherein: The plurality of fiber sheets are integrated with the foamed resin molded body.

5. The foamed resin thermal insulation material according to claim 1 or 2, wherein: The cellulose nanofiber powder is mixed into the foamed resin molded body to form an integrated body.

6. The foamed resin thermal insulation material according to claim 1 or 3, wherein: The negative thermal expansion material is selected from zirconium tungstate phosphate (Zr2WO4(PO4)2), zirconium sulfate phosphate (Zr2SP2O 12 ), one of the oxide ceramics BiNi1-xFexO3 with a perovskite structure composed of bismuth-nickel-iron, zirconium tungstate (ZrW2O8), and silicon oxide (Li2O-Al2O3-nSiO2), the unfoamed resin material is one selected from unfoamed polyurethane resin, unfoamed polystyrene resin, unfoamed polyethylene resin, unfoamed polyester resin, and unfoamed phenolic resin, and the fiber sheet is a cloth selected from glass fiber, carbon fiber, and aromatic polyamide fiber.

7. The foamed resin thermal insulation material according to claim 3, wherein: The negative thermal expansion material is zirconium tungstate phosphate (Zr2WO4(PO4)2), The unfoamed resin material is an unfoamed polyurethane resin. The fiber sheet is a cloth made of glass fiber. The cellulose nanofiber powder is mixed into the foamed resin molded body to form an integrated body, and the negative thermal expansion material is mixed in an amount of 0.75 vol % or more based on the volume of the foamed resin molded body.

8. The foamed resin thermal insulation material according to claim 3, wherein: The negative thermal expansion material is zirconium tungstate phosphate (Zr2WO4(PO4)2), The unfoamed resin material is an unfoamed polyurethane resin. The fiber sheet is a cloth made of glass fiber. The foamed resin molded body is integrated with 3 wt % or more of cellulose nanofiber powder relative to the amount of the unfoamed resin filled.

9. The foamed resin thermal insulation material according to claim 3, wherein: The negative thermal expansion material is zirconium tungstate phosphate (Zr2WO4(PO4)2), The unfoamed resin material is an unfoamed polyurethane resin. The fiber sheet is a cloth made of glass fiber. In the foamed resin molded body, more than 1wt% of cellulose nanofiber powder is mixed into the body relative to the amount of filled unfoamed resin, and further, multiple layers of fiber sheets composed of mutually crossed warp and weft yarns are integrated with each other, and more than 0.75vol% of the negative thermal expansion material is mixed into the body relative to the volume of the foamed resin molded body.

10. A method for preparing a foamed resin thermal insulation material, wherein: A negative thermal expansion material composed of zirconium tungstate phosphate (Zr2WO4(PO4)2) is mixed into an unfoamed polyurethane resin, and the unfoamed resin material in this state is filled into a mold in a layered manner with a fiber sheet of glass cloth composed of intersecting warp and weft yarns, and is foamed and cured in the mold to form a shape.

Citation Information

Patent Citations

  • Heat insulation method for pipe

    JP2016176511A

  • Application of heat insulating materials to low temperature equipment and foamed moldings used for the application

    JP1998076543A

  • Heat insulation structure

    JP2000249291A

  • Foamed molding

    JP2008247973A

  • Adhesive agent for electronic parts

    JP2008260892A